Homeostasis Imbalance in the Endometrium of Women with Implantation Defects: The Role of Estrogen and Progesterone - Lessey, Bruce A.; Young, Steven L. (Seminars in Reproductive Medicine, 2014)
Embryo implantation is regulated by an inflammatory process in response to sequential exposure to estrogen and progesterone, followed by resolution and repair. The actions of estrogen and progesterone on these inflammatory processes are tightly and reciprocally controlled through regulated expression of steroid receptors, cofactors, chaperone proteins, and downstream signaling components. In endometriosis, the inflammatory cascades, normally seen at menstruation, are prematurely activated and endogenous endometrial mechanisms of inflammation resolution appear defective. The temporally abnormally inflammation is also associated with an imbalance between estrogen and progesterone actions; the normal luteal-phase dominance of progesterone action appears to be lost and is replaced by progesterone resistance and estrogen dominance. In this review, we examine these relationships in greater detail and argue that estrogen action is a prime target for future therapeutic solutions to endometriosis and implantation failure that result from this chronic, inflammatory disease.
Keywords: menstrual cycle; endometrium; infertility; endometriosis; progesterone and estrogen